Los fundamentos éticos de las cosmologías indígenas - Stefano Varese (Les Cahiers ALHIM)
This article proposes to analyze the ethical and rational foundations of the Indigenous Peoples of the Americas’ relations with nature-world. The premise is the radical critique of Western anthropocentric reason including the neo-liberal and neo-colonial vicissitudes of the socio-ideological complex of modernity-colonialism-capitalism. In the agrarian or foraging Indigenous People’s ethics, nature has an axiological function within the culture favoring the daily collective task of survival and development of the whole human group and “all its relatives”. Sumak kawsay (or the Good Life) of the Kichwa/Quechua and Kametsa asaike (or the knowledge that allows for a Good Life in harmony) of the Ashaninka would be the ethical foundations of indigenous collective life. It is based on these ethical foundations that articulate life on earth that Indigenous People have resisted against genocide, Euroamerican invasions and the mental colonialism of national bourgeoisies.